Treatment patterns and economic burden of bacterial vaginosis among commercially insured women in the USA - Eren Watkins; Clifton M Chow; Melissa Lingohr-Smith; Jay Lin; Candice Yong; Krishna Tangirala; Kevin Collins; James Li; Roy Brooks; Jennifer Amico (Journal of Comparative Effectiveness Research, 2023)
Aim: Bacterial vaginosis (BV) is a common vaginal dysbiosis associated with adverse clinical sequelae, most notably, increased risk of sexually transmitted infections (STIs). The aims of this study were to estimate the frequency of BV recurrence, treatment patterns, other gynecological (GYN) conditions, and the associated healthcare resource utilization (HCRU) and costs among commercially insured patients in the USA. Patients & methods: Female patients aged 12–49 years with an incident vaginitis diagnosis and ≥1 pharmacy claim for a BV medication (fungal treatment only excluded) were selected from the Merative™ MarketScan commercial database (2017–2020). During a minimum 12-month follow-up, additional treatment courses, treatment patterns, frequency of other GYN conditions, and HCRU and costs were assessed. Generalized linear models were used to identify baseline predictors of total all-cause healthcare costs and number of treatment courses. Results: The study population included 140,826 patients (mean age: 31.5 years) with an incident vaginitis diagnosis and ≥1 BV medication claim. During the follow-up, 64.2% had 1 treatment course, 22.0% had 2, 8.1% had 3, and 5.8% had ≥4; 35.8% had a BV recurrence (≥2 BV medication claims). The most commonly prescribed BV medication was oral metronidazole (73.6%). Approximately 12% (n = 16,619) of patients had a new diagnosis of another GYN condition in the follow-up; 8.2% had a new STI, which were more common among patients with ≥4 treatment courses (12.9%). During follow up, total all-cause healthcare costs averaged $8987 per patient per year (PPPY) of which $470 was BV related. BV-related healthcare costs increased from $403 PPPY among those with 1 treatment course to $806 PPPY among thosewith≥4with nearly half the costs attributed to outpatient office visits. Conclusion: BV recurrence among this population represented a substantial clinical and healthcare economic burden warranting improvements in women’s healthcare.